2017
DOI: 10.1103/physrevlett.118.239602
|View full text |Cite
|
Sign up to set email alerts
|

Zhao et al. Reply

Abstract: Zhao et al. Reply In the first sentence of the Comment [1], the authors refer to four systems: GaNð10 10Þ-1H, ZnOð10 10Þ-1H, GaNð10 10Þ-Li, and ZnOð10 10Þ-1Li. In the second sentence, the authors claim to demonstrate that "a charge-density-wave (CDW) phase is due to the artifact of the generalized gradient approximation (GGA), while the antiferromagnetic (AFM) ground state is predicted by the hybrid DFT calculation…" The Comment contains a single table, showing the total energy of the GaNð10 10Þ-1H system only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
66
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 9 publications
(2 reference statements)
7
66
0
Order By: Relevance
“…[43] Intercalation with Cu atoms shifts the chemical potential of 1T-TiSe 2 by 0.1 eV. [53,54] Since the circumstances in the pristine material are nearly ideal for the formation of excitons, they deteriorate quickly upon intercalation, leaving a dominant role for the phonons in the CDW formation in this part of the phase diagram. As explained above, such a scenario naturally leads to a superconducting dome centered around the critical value of intercalation.…”
Section: Hybrid Phonon-exciton Modelmentioning
confidence: 99%
“…[43] Intercalation with Cu atoms shifts the chemical potential of 1T-TiSe 2 by 0.1 eV. [53,54] Since the circumstances in the pristine material are nearly ideal for the formation of excitons, they deteriorate quickly upon intercalation, leaving a dominant role for the phonons in the CDW formation in this part of the phase diagram. As explained above, such a scenario naturally leads to a superconducting dome centered around the critical value of intercalation.…”
Section: Hybrid Phonon-exciton Modelmentioning
confidence: 99%
“…The further lattice relaxation of p(2×2) gives ∆E = −0.57 eV and E g = 0.99 eV. Interestingly, a ferromagnetic (FM) phase appears in metallic p(1×1), but such spin ordering disappears in semiconducting p(1×2) and p(2×2) [1]. This disappearance of magnetic order may be due to the fact that the local density approximation or GGA tends to stabilize artificially delocalized electronic states due to their inherent self-interaction error (SIE) [2].…”
mentioning
confidence: 99%
“…For the 1D metallic structure composed of the surface metal atoms (Ga or Zn), Zhao et al [1] found that the semiconducting p(1×2) phase with alternately up-and-down displacements is more stable than the metallic p(1×1) phase, and the p(2×2) phase is further stabilized. The relative total energies (∆E) of these phases for GaN(1010)-1H are listed in Table I.…”
mentioning
confidence: 99%
See 2 more Smart Citations